Secular trends and determinants of ad libitum energy intake measured in a research setting from 1999-2020 - Ahern, Mary M.; Stinson, Emma J.; Piaggi, Paolo; Krakoff, Jonathan; Votruba, Susanne B. (Frontiers in Nutrition, 2024)
Introduction Historically, secular and seasonal trend analyses have been examined using self-report measures of intake. Rarely are objective measures and known determinants of dietary intake used in these analyses. Our objective was to quantify the seasonal and secular differences in an objective ad libitum intake paradigm while considering the contribution of determinants, such as fat-free mass (FFM) index and spontaneous physical activity (SPA) limited to the restricted space of a whole-room calorimeter. Methods For this study, recruitment of N = 292 healthy, diabetes free, adults occurred from 1999 to 2020. Assessment during their 10-day stay included body composition (by DXA), SPA (by an approximately 24-h stay in whole-room calorimetry), and ad libitum intake (by a vending machine for 3 days). This secondary analysis used general linear models (GLM) to investigate secular and seasonal differences while adjusting for sex, age, FFM index, FM (fat mass) index, SPA, and race/ethnicity. Results FFM index and SPA were positively associated with all intake measures (p < 0.05). In all adjusted seasonal models, season did not affect intake. Adjusted secular trends models (kcals/year) demonstrated a decrease in total kcals (β = −55), intake as percent weight maintaining energy needs (β = −2), protein kcals (β = −10), fat kcals (β = −27), and carbohydrates kcals (β = −22) (all p < 0.05). After further adjustment for SPA, significance remained in all intake measures (p < 0.05). Secular trends in body composition revealed no changes in weight, BMI, and percent body fat (all p > 0.20). Discussion Our results indicate that over time, ad libitum intake decreased in this controlled research setting and remained significant even after accounting for positive determinants of intake. A significant ad libitum decrease, coupled with no change in body composition, may highlight a participant bias toward calorie restriction in a controlled setting over time and deserves further investigation.